2019
DOI: 10.3390/app9173495
|View full text |Cite
|
Sign up to set email alerts
|

SEVUCAS: A Novel GIS-Based Machine Learning Software for Seismic Vulnerability Assessment

Abstract: Since it is not possible to determine the exact time of a natural disaster’s occurrence and the amount of physical and financial damage on humans or the environment resulting from their event, decision-makers need to identify areas with potential vulnerability in order to reduce future losses. In this paper, a GIS-based open source software entitled Seismic-Related Vulnerability Calculation Software (SEVUCAS), based on the Step-wise Weight Assessment Ratio Analysis (SWARA) method and geographic information sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 102 publications
0
30
0
Order By: Relevance
“…Scientists have used a variety of computational data mining methods and models in natural hazard research, including studies of floods [18][19][20][21][22][23][24][25][26][27][28], wildfire [29], sinkholes [30], droughtiness [31,32], earthquakes [33,34], land/ground subsidence [35,36], groundwater [21,[37][38][39][40][41][42][43][44], and landslides [22,. These methods extract related patterns in historical data to predict future events [73].…”
Section: Introductionmentioning
confidence: 99%
“…Scientists have used a variety of computational data mining methods and models in natural hazard research, including studies of floods [18][19][20][21][22][23][24][25][26][27][28], wildfire [29], sinkholes [30], droughtiness [31,32], earthquakes [33,34], land/ground subsidence [35,36], groundwater [21,[37][38][39][40][41][42][43][44], and landslides [22,. These methods extract related patterns in historical data to predict future events [73].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Van Dao et al [3] reported that deep learning ANN requires much more computational time than conventional methods. Despite this disadvantage, machine learning methods have the ability to handle large volumes of non-linear and complex data derived from different sources and reported at a variety of scales in many fields especially in studies of natural hazards such as floods [18][19][20][21][22][23][24][25][26][27][28], wildfires [29,30], sinkholes [31], drought [32,33], earthquakes [34,35], gully erosion [36,37], and land/ground subsidence [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments of machine learning (ML) have introduced new optimization algorithms, which could be used for optimizing weights for membership function of the neural fuzzy model. Furthermore, ML techniques have recently gained a good attention among environmental modeling research community as they are advantageous in efficiently capturing the complex relationship between the environmental predictors and the response, such as flood [55][56][57][58][59][60][61][62][63], earthquake [64,65], wildfire [66], sinkhole [67], droughtiness [68], gully erosion [69,70], groundwater [71][72][73][74] and land/ground subsidence [75], and landslide in this case [54,59,. Nevertheless, investigation of new optimization algorithms and the neural fuzzy has not been carried out.…”
Section: Introductionmentioning
confidence: 99%